Tinjauan Yuridis Terhadap Anggota Koperasi Dalam Hal wanprestasi Atas Pelaksanaan Perjanjian Kredit Pada Koperasi Unit Desa - Jihan Fadila; Zaini Munawir; Marsella Marsella (Universitas Medan Area, 2022)
In the process of granting credit, it is often the case that the creditor is detrimental when the debtor defaults, so we need a rule contained in a credit agreement that aims to provide certainty for the related parties. The research objectives to be achieved in this study are to determine the procedure for implementing credit agreements, to determine dispute resolution when a member of a cooperative defaults in a credit agreement, to find out the legal consequences if a member of a cooperative defaults in a credit agreement. The research method used is Library Research and Field Research. Juridical research type normative. The conclusion obtained is the procedure contained in KUD